Silicon Foliar Application Mitigates Salt Stress in Sweet Pepper Plants by Enhancing Water Status, Photosynthesis, Antioxidant Enzyme Activity and Fruit Yield - Khaled A. A. Abdelaal; Yasser S.A. Mazrou; Yaser M. Hafez (Plants, 2020)
Silicon is one of the most significant elements in plants under abiotic stress, so we investigated the role of silicon in alleviation of the detrimental effects of salinity at two concentrations (1500 and 3000 ppm sodium chloride) in sweet pepper plants in two seasons (2018 and 2019). Our results indicated that relative water content, concentrations of chlorophyll a and b, nitrogen, phosphorus and potassium contents, number of fruits plant−1, fruit fresh weight plant−1 (g) and fruit yield (ton hectare−1) significantly decreased in salt-stressed sweet pepper plants as compared to control plants. In addition, electrolyte leakage, proline, lipid peroxidation, superoxide (O2−) and hydrogen peroxide (H2O2) levels, soluble sugars, sucrose, and starch content as well as sodium content significantly increased under salinity conditions. Conversely, foliar application of silicon led to improvements in concentrations of chlorophyll a and b and mineral nutrients, water status, and fruit yield of sweet pepper plants. Furthermore, lipid peroxidation, electrolyte leakage, levels of superoxide, and hydrogen peroxide were decreased with silicon treatments.